British Romanticism and the Jews
XII, 294 p.
Keywords: British Romanticism and the Jews explores the mutual influences exerted by the British-Christian and British-Jewish communities on each other during the period between the Enlightenment and Victorianism. The essays in the volume demonstrate how the texts produced by the Jewish Enlightenment provided a significant resource for romantic intellectual revisionism, in much the same way that British romanticism provided the cultural basis through which the British-Jewish community was able to negotiate between the competing obligations to ethnicity and nationalism.